1993
DOI: 10.1039/dt9930002929
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent gold(I) acetylide complexes. Photophysical and photoredox properties and crystal structure of [{Au(CCPh)}2(µ-Ph2PCH2CH2PPh2)]

Abstract: The spectroscopic and photophysical properties of three gold( 1)-acetylide complexes [N (PPh,),] -[Au(CzCPh),], [Au(PPh,)(C-CPh)] and [{Au(C-CPh)},(p-dppe)] [dppe = 1,2-bis(diphenyIphosphino)ethane] are described. X-Ray crystal analysis of the latter showed a weak metal-metal interaction in the solid state with the shortest Au -Au separation being 3.1 53(2) A. The gold(1)acetylide complexes have long-lived and emissive ,(n,n*) excited states in solutions at room temperature. The photoreaction of [Au( PPh,) (C-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
90
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(108 citation statements)
references
References 17 publications
16
90
2
Order By: Relevance
“…8 The 1 H and 13 C NMR spectra of the compounds were in accord with the symmetrical structure shown in Chart 1. However, it was not possible to resolve signals in any of the 13 C NMR spectra for the alkyne carbon atoms.…”
Section: Synthesis and Solution Characterizationsupporting
confidence: 52%
See 1 more Smart Citation
“…8 The 1 H and 13 C NMR spectra of the compounds were in accord with the symmetrical structure shown in Chart 1. However, it was not possible to resolve signals in any of the 13 C NMR spectra for the alkyne carbon atoms.…”
Section: Synthesis and Solution Characterizationsupporting
confidence: 52%
“…[ 3 -7 ] Among the first photoemissive gold(I) alkynyl complexes to be described in the literature were Ph 3 PAuC≡CPh and {PhC≡CAu} 2 (µ-dppe) (dppe = Ph 2 PCH 2 CH 2 PPh 2 ). Che and coworkers [8] showed that these species possessed long-lived and emissive excited states in CH 2 Cl 2 solution at ambient temperature, and upon going from solution to the solid state, a dramatic red shift in the emission maximum of {PhC≡CAu} 2 (µ-dppe) was observed. The presence of short (≈3.00-3.20 Å) Au...Au contacts in the solid state is thought to be fundamental to emissive behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…276 and 289 nm. Based on studies of related species [21,[35][36][37][38] the transitions that give rise to the observed absorption spectra are most likely to be tpy/alkyne π*←π with Au orbital participation. When irradiated at 289 nm, 4'-ethynyl-2,2':6',2"-terpyridine emits at 351 nm with a high energy shoulder at 342 nm.…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“…5 and Supplementary Discussion) 22,23 . X-ray Diffraction together with cyclic voltammetry studies showed that while 5a presents aurophilic bonding between two gold atoms 14 , 5c has no aurophilic bonds at all 14 and 5b has an intermediate behaviour, depending on the counteranion 24,25 . The results indicate that aurophilic bonding has a positive influence on the reaction rate but none on the distal size selectivity.…”
Section: Resultsmentioning
confidence: 99%